MANAJEMEN STRATEGIK DALAM MENINGKATKAN MUTU MADRASAH TSANAWIYAH NURUL ULUM TELUK TIRAM DARAT BANJARMASIN - Achmad Fauzi (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2019)
The research is motivated by the phenomenon that education should be managed with the strategic management in order to choose among the many good management to produce the most good management to be developed. School-based Strategic Management are granting broad autonomy at the school level so that schools can freely manage resources and to allocate funds according to priority needs, as well as more responsive to local needs. So in other words that the principal of the school as a manager is given full authority to be able to optimize the existing resources at the school in order to improve the quality of the quality of his school. Formulation of the problem in this research are (1) How strategic planning at Madrasah Nurul Ulum Teluk Tiram Darat Banjarmasin ? (2) How do strategic implementation in Madrasah Nurul Ulum Teluk Tiram Darat Banjarmasin ? (3) How strategic evaluation in improving the quality of MTs Nurul Ulum Teluk Tiram Darat Banjarmasin ? Processing of writing this research , researchers using qualitative approach with the design of multi studies the case. Findings and theories presented by using a phenomenological foundation of thinking, while the informant was selected by using the technique of snowball sampling, through the data search process and the informant from one switch to another informant on the advice of a previous informant fit the purpose and framework of research. Data collection was carried out with interview techniques, observation, and documentation. The data obtained are then analyzed by using data reduction techniques, followed by the presentation of the data, as well as the withdrawal of conclusion/verify. Checking the validity of the data using the technique of credibility, transfarbility, dependenbility, and confirmability. The results of the research in this study are: (1) the formulation of strategy in Madrasah Nurul Ulum Teluk Tiram Darat Banjarmasin done by first formulating a vision and mission through the analysis of the internal and external environment. (2) MTs Nurul Ulum Teluk Tiram Darat Banjarmasin implements the program of the formulation of strategies that have been arranged in advance (3) Evaluation strategy in MTs Nurul Ulum Teluk Tiram Darat Banjarmasin carried out, namely: (a) an evaluation of the present leadership of the head of school/madrasah with representatives do representatives with the intensity of the time often. (b) a thorough evaluation was carried out by whole the Board of teachers and employees each month and at the beginning and end of the semester.